Psychiatric Symptoms in Amyotrophic Lateral Sclerosis: Beyond a Motor Neuron Disorder - Zucchi, Elisabetta; Ticozzi, Nicola; Mandrioli, Jessica (Frontiers in Neuroscience, 2019)
The historical view that Amyotrophic Lateral Sclerosis (ALS) as a pure motor disorder has been increasingly challenged by the discovery of cognitive and behavioral changes in the spectrum of Frontotemporal Dementia. Less recognized and still significant comorbidities that ALS patients may present are prior or concomitant psychiatric illness, such as psychosis and schizophrenia, or mood disorders. These non-motor symptoms disturbances have a close time relationship with disease onset, may constitute part of a larger framework of network disruption in motor neuron disorders, and may impact ALS patients and families, with regards to ethical choices and end-of-life decisions. This review aims at identifying the most common psychiatric alterations related to ALS and its prognosis, looking at a common genetic background and shared structural brain pathology.